KARAKTER KEWIRAUSAHAAN GURU SMA NEGERI KECAMATAN TAMBANG, KABUPATEN KAMPAR - Suarman '; D. Ayub ' (PEKBIS, 2017)
The character development of entrepreneurship in formal education in line with thenational policy in the field of education, which has prepared the concept ofentrepreneurship-based curriculum for all levels of education. The researchobjective was to assess the entrepreneurial character of teachers SMA NegeriKecamatan Tambang, Kampar district. This is a descriptive quantitative researchconducted by survey. The sample was 114 teachers. Data were collected using aquestionnaire which is based on Likert scale of five options, and the data wereanalyzed using descriptive statistics and statistical inference. This study found thatthe entrepreneurial character of teachers SMA Negeri Kecamatan Tambang,Kampar district viewed by 16 indicators obtained very high value Mean 4, 27 andStandard Deviasi 0.86. Meaning, the entrepreneurial character of teachers has beenvery good, all the indicators are already owned by the teacher with an excellent andvery high, but still needs to be improved by strengthening the entrepreneurialcharacter in the learning activities, with the coaching aspects relating to indicators.The results of this study will be as well as teaching materials and self-improvementof the entrepreneurial character, especially in the educational institution, teachersand students, in order to realize the will of Law Number 20 Year 2003 on NationalEducation System Article 3, which states that the national education serves todevelop skills and character development and civilization of the nation's dignity inthe context of the intellectual life of the nation, aims to develop the potential oflearners to be a man of faith and fear of God Almighty, noble, healthy,knowledgeable, skilled, creative, independent, and become citizens democratic andresponsible.